Peran Disdukcapil Kabupaten Aceh Selatan Dalam Meningkatkan Kepemilikan Akta Kelahiran - Pitri Wahyuni; Ikhsan Ikhsan (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2022)
Nationally, deed ownership in 2021 reached 88.42%, lower than in 2020 which reached 93.78%. Population administration has been carried out at the South Aceh Disdukcapil so that children who are born are registered with their citizenship in order to protect their rights to live and develop and provide legal guarantees of citizenship as Indonesian citizens. This study aims to determine the role of the Department of Population and Civil Registration in increasing birth certificate ownership regarding the importance of making birth certificates for children, as well as being able to provide information to the public to carry out population administration. This study uses a qualitative method with a descriptive approach. The results of the study show that the South Aceh Disdukcapil has played an important role in increasing the ownership of birth certificates. This is also evidenced by the ownership of birth certificates which continues to increase every year.